Culex genome is not just another genome for comparative genomics - Reddy BP; Labbé Pierrick; Corbel Vincent (Parasites & Vectors, 2012)
Abstract Formal publication of the Culex genome sequence has closed the human disease vector triangle by meeting the Anopheles gambiae and Aedes aegypti genome sequences. Compared to these other mosquitoes, Culex quinquefasciatus possesses many specific hallmark characteristics, and may thus provide different angles for research which ultimately leads to a practical solution for controlling the ever increasing burden of insect-vector-borne diseases around the globe. We argue the special importance of the cosmopolitan species- Culex genome sequence by invoking many interesting questions and the possible of potential of the Culex genome to answer those.